2023
DOI: 10.3389/fmicb.2023.1261651
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the function of ESCRT and its role in enveloped virus infection

Chunxuan Wang,
Yu Chen,
Shunlin Hu
et al.

Abstract: The endosomal sorting complex required for transport (ESCRT) is an essential molecular machinery in eukaryotic cells that facilitates the invagination of endosomal membranes, leading to the formation of multivesicular bodies (MVBs). It participates in various cellular processes, including lipid bilayer remodeling, cytoplasmic separation, autophagy, membrane fission and re-modeling, plasma membrane repair, as well as the invasion, budding, and release of certain enveloped viruses. The ESCRT complex consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 220 publications
(208 reference statements)
0
2
0
Order By: Relevance
“…Knockdown of signal transducing adapter molecule 1 (STAM) results in increased length of cell projections 67 , suggesting that STAM is inhibitory. STAM is a component of the endosomal sorting complexes required for transport (ESCRT)-0 complex that mediates membrane remodelling, vesicular transport and autophagy, and is hijacked by enveloped viruses to mediate budding 68 . STAM was cleaved by 3CL pro (Extended Data Fig.…”
Section: Sars-cov-2 Infection Induces Translocation Of Centrosomal Pr...mentioning
confidence: 99%
“…Knockdown of signal transducing adapter molecule 1 (STAM) results in increased length of cell projections 67 , suggesting that STAM is inhibitory. STAM is a component of the endosomal sorting complexes required for transport (ESCRT)-0 complex that mediates membrane remodelling, vesicular transport and autophagy, and is hijacked by enveloped viruses to mediate budding 68 . STAM was cleaved by 3CL pro (Extended Data Fig.…”
Section: Sars-cov-2 Infection Induces Translocation Of Centrosomal Pr...mentioning
confidence: 99%
“…As previously discussed, specific viral proteins exploit the exosome biogenesis pathway to facilitate virus budding. It has been shown that transmembrane subunits of viral envelope proteins, including those of HIV, can interact with components of the ESCRT machinery, such as TSG101 [ 264 ]. These properties, which are found in the proteins of various viruses (e.g., the VSV-G protein or the Nef protein of HIV), have been exploited to direct proteins of interest to exosomes [ 265 ].…”
Section: Exosomes and Antigen Presentation: Perspectives In Vaccinologymentioning
confidence: 99%
“…HSV-1 is a nervous system pathogen, which uses its own virus-encoded protein and host ESCRT mechanism to promote viral budding ( Button et al., 2020 ). Unlike other enveloped viruses, HSV-1 does not require TSG101 or ALIX, a protein containing the Bro1 domain, to recruit or activate ESCRT-1 ( Wang C. et al., 2023 ). HSV-1 capsid uses nucleoplasmic ESCRT to obtain a lipid envelope from the inner nuclear membrane (INM) and then fuses with the outer nuclear membranes (ONM) ( Wilhelmsen et al., 2005 ).…”
Section: The Role Of Exosomes In Virus Infectionmentioning
confidence: 99%